2021
DOI: 10.1111/ijcp.14786
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of hospitalised COVID‐19 patients and parameters associated with severe pneumonia

Abstract: All the authors are members of Turkish Respiratory Society (TRS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
2
6
0
2
Order By: Relevance
“…However, when patients with severe COVID-19 were grouped separately, it was observed that the mean age increased to 60.3 and the male sex ratio increased to 60%. Our mean age in the patients we followed up after severe and critical COVID-19 is similar to Turan et al's study [21].…”
Section: Discussionsupporting
confidence: 88%
“…However, when patients with severe COVID-19 were grouped separately, it was observed that the mean age increased to 60.3 and the male sex ratio increased to 60%. Our mean age in the patients we followed up after severe and critical COVID-19 is similar to Turan et al's study [21].…”
Section: Discussionsupporting
confidence: 88%
“…The study cohort reflects the well described characteristics of hospitalised patients with COVID-19, with a male dominance, middle-aged and older individuals, presence of co-morbidities such as CVD, chronic pulmonary disease, obesity, and diabetes (56)(57)(58). Although these conditions are known risk factors for severe COVID-19, somewhat surprisingly, we did not find a significant association of co-morbidities, besides obesity, with disease severity.…”
Section: Discussionmentioning
confidence: 60%
“…The results of various studies have shown a link between values of blood factors with high blood pressure [ 29 31 ] and COVID-19 [ 32 ]. Meanwhile, these factors can be considered as predictors of hypertension [ 33 ] or severity of COVID-19 [ 34 ]. Among these, we can mention the inflammatory factors such as C-reactive protein (CRP) that have been shown to be associated with both hypertension and COVID-19 disease [ 35 – 37 ].…”
Section: Discussionmentioning
confidence: 99%